Impact of architectural design on mental health outcomes in psychiatric hospitals - Tendolkar, Ketki Bharat; Kalia, Raman; Charan, Gopal Singh; Kaur, Maninderjit; Kaur, Kawaljeet (Journal of Gandaki Medical College-Nepal, 2025)
The impact of hospital architecture on mental health outcomes in psychiatric care has gained increasing attention. This review examines vital architectural elements—natural light, biophilic design, and noise control—and their effects on patient well-being and recovery. Salutogenic designs, which focus on enhancing health and well-being, have reduced stress, improved mood, and supported cognitive function. Incorporating green spaces and natural materials can mitigate symptoms of depression and anxiety while enhancing the quality of care. Additionally, noise management and ergonomic workspace design improve the mental health of healthcare staff, reducing burnout and increasing efficiency. However, further research is required to understand the influence of less-studied design elements like geometric shapes and pareidolia. This review highlights the need for interdisciplinary collaboration between architects and healthcare professionals to optimize hospital designs that support recovery and well-being in psychiatric settings.